2017
DOI: 10.1021/acs.jpcc.7b00347
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photochemical Control of Doping Levels in Supported Graphene

Abstract: Controlling the type and density of charge carriers in graphene is vital for a wide range of applications of this material in electronics and optoelectronics. To date, chemical doping and electrostatic gating have served as the two most established means to manipulate the carrier density in graphene. Although highly effective, these two approaches require sophisticated graphene growth or complex device fabrication processes to achieve both the desired nature and the doping densities with generally limited dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 68 publications
(146 reference statements)
0
40
0
Order By: Relevance
“…For the typical doping levels for substrate‐supported graphene, resulting in a Fermi energy on the order of 100 meV (see, e.g., refs. ), the interband THz transitions are Pauli‐blocked even at T = 0, leaving only the intraband transitions described by the free carrier conductivity of Equation possible.…”
Section: Light–matter Interaction In Graphene In the Linear Regimementioning
confidence: 99%
See 2 more Smart Citations
“…For the typical doping levels for substrate‐supported graphene, resulting in a Fermi energy on the order of 100 meV (see, e.g., refs. ), the interband THz transitions are Pauli‐blocked even at T = 0, leaving only the intraband transitions described by the free carrier conductivity of Equation possible.…”
Section: Light–matter Interaction In Graphene In the Linear Regimementioning
confidence: 99%
“…We note that most single‐layer graphene samples are in fact unintentionally doped due to impurities induced in the preparation process as well as the effects of the environment in which graphene is used . For example, in the course of preparation of chemical vapor deposition (CVD) grown graphene, which is one of the most popular graphene forms broadly available nowadays, hole‐doping is induced during the transfer of poly(methyl methacrylate) (PMMA)‐covered graphene from copper foils to dielectric substrates by residues of PMMA .…”
Section: Light–matter Interaction In Graphene In the Linear Regimementioning
confidence: 99%
See 1 more Smart Citation
“…The ultrafast energy relaxation dynamics of graphene have been studied experimentally using optical pump -optical probe spectroscopy [21][22][23][24][25][26], time-resolved ARPES measurements [27,28], time-resolved photocurrent scanning microscopy [29][30][31], optical pump -terahertz (THz) probe spectroscopy [32][33][34][35][36][37][38][39][40][41][42][43][44] and high-field THz spectroscopy [6,45]. These time-resolved studies have identified that the energy relaxation dynamics of the photoexcited carriers consist mainly of carrier-carrier scattering and coupling to optical, acoustic and remote substrate phonons.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to such uncontrolled alterations of graphene's electronic properties, a promising approach to tailor the band structure and the charge carrier properties is doping by heteroatoms, which are either incorporated in the lattice replacing carbon atoms, or physisorbed to the graphene surface while leaving the lattice intact . Combining both approaches, allows for flexible transitions between n‐ and p‐type doping in the same crystal, which demonstrates the versatility of changing the electronic properties in graphene by controlling the degree of doping . Furthermore, heteroatomic doping has even the potential to open up a band gap .…”
Section: D: Doped and Undoped Graphenementioning
confidence: 99%